2019
DOI: 10.1177/1934578x19857900
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Volatile Constituents of Ginkgo Leaf

Abstract: Ginkgo biloba L. (Ginkgoaceae) is one of the oldest trees on earth. The medicinal use of its seeds and leaves has been a tradition for thousands of years. The standardized extract (known as EGb 761) contains several biologically active components, among them are terpenes and flavonoid glycosides that are responsible for the pharmacological activities of Ginkgonis folium. According to European Union herbal monographs (EUHM), the leaves of Ginkgo are recommended for the treatment of dementia, cerebral vascular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Hortorum Cultus, 22(1), 95-106. https://doi.org/10.24326/asphc.2023.4621 as well as jasmonic acid and 12-oxo-phytodienoic acid, an intermediate metabolite in JAs biosynthesis [Saniewski et al 2020]. Moreover, recently Czigle et al [2019] demonstrated in the volatile constituent in G. biloba leaves the presence of linolenic acid methyl ester, whose biosynthesis may be related to the loss of C18:3 observed in our study during senescence of G. biloba leaves. These reasons are possible contributors to the observed decline in linolenic acid, and should be taken into account in explaining the causes of this phenomenon.…”
Section: Discussionsupporting
confidence: 50%
“…Hortorum Cultus, 22(1), 95-106. https://doi.org/10.24326/asphc.2023.4621 as well as jasmonic acid and 12-oxo-phytodienoic acid, an intermediate metabolite in JAs biosynthesis [Saniewski et al 2020]. Moreover, recently Czigle et al [2019] demonstrated in the volatile constituent in G. biloba leaves the presence of linolenic acid methyl ester, whose biosynthesis may be related to the loss of C18:3 observed in our study during senescence of G. biloba leaves. These reasons are possible contributors to the observed decline in linolenic acid, and should be taken into account in explaining the causes of this phenomenon.…”
Section: Discussionsupporting
confidence: 50%
“…The constituents were hydrocarbons, esters, aldehydes, ketones, and acids. 21 The ionones were detected only in one young tree and limonene only in the old one. 21…”
mentioning
confidence: 95%
“…The constituents were hydrocarbons, esters, aldehydes, ketones, and acids. 21 The ionones were detected only in one young tree and limonene only in the old one. 21 G. biloba green leaves have been used for the extraction of biologically active compounds using various extraction techniques.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Quality control of Ginkgo biloba L. extracts and leaves can be routinely carried out by reversedphase HPLC (RP-HPLC) with evaporative light scattering detection (ELSD) (Dubber & Kanfer, 2006;Kaur et al, 2009), refractive index (RI) (Wang & Ju, 2000), diode array detector (DAD) (Tang et al, 2010) and mass spectrometry detection (Wang et al, 2017). As an orthogonal technique gas chromatography (GC) system equipped with a flame ionization detector (FID) or mass spectrometry (MS) detection (Czigle et al, 2019) is also used. At sample preparation steps; cold and hot extraction, pressurized solvent extraction and ultrasoundassisted extraction is typically applied to achieve the simultaneous analysis of terpene trilactones and flavonol aglycones (Kaur et al, 2009;Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%